IDENTIFY UZBEK GESTURES USING ARTIFICIAL INTELLIGENCE - Lazizkhon Farkhadovich Nasirov; Farkhod Odilovich Nosirov; Madina Valisherovna Nosirova (Web of Journals Publishing, 2024)
The article discusses Uzbek gesture recognition using artificial intelligence (AI) technology. It is aimed at analyzing existing methods in AI and developing effective solutions to improve communication among hearing-impaired people.
Keywords: Artificial Intelligence, Uzbek Sign Language, Machine Learning, Convolutional Neural Networks, RNN, LSTM.